2005
DOI: 10.1158/1078-0432.ccr-04-1610
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Effects of Tamoxifen Plus Exemestane in Postmenopausal Women with Breast Cancer

Abstract: Purpose: In some specific circumstances, combined hormonal therapies for breast cancer seem to be more effective than single maneuvers. In two laboratory mammary cancer models, the combination of the aromatase inactivator exemestane plus tamoxifen gives a higher response rate than is found with either agent alone.To evaluate the endocrine effects of the combination of exemestane and tamoxifen, we studied 33 postmenopausal women disease-free following primary treatments for breast cancer who were taking tamoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Because exemestane also reduced ALP in the femoral epiphysis, it is discernible that it may impair bone formation in femoral epiphysis while having no effect on bone resorption. Thus, there seems to be a differential profile of the two aromatase inhibitors on bone biomarkers which is also in agreement with some previous reports [6,45]. However, our results differ from the study by McCloskey and co-workers (2007) which reported all three aromatase inhibitors viz.…”
Section: Discussionsupporting
confidence: 89%
“…Because exemestane also reduced ALP in the femoral epiphysis, it is discernible that it may impair bone formation in femoral epiphysis while having no effect on bone resorption. Thus, there seems to be a differential profile of the two aromatase inhibitors on bone biomarkers which is also in agreement with some previous reports [6,45]. However, our results differ from the study by McCloskey and co-workers (2007) which reported all three aromatase inhibitors viz.…”
Section: Discussionsupporting
confidence: 89%
“…A portion of the plasma aliquots from the week 4 and week 12 blood samples was separated and assayed for estrone, estrone sulfate, and estradiol concentrations, as well as for osteocalcin, total and HDL cholesterol, triglycerides, and alkaline phosphatase. The results of the enzyme, lipid, and bone resorption assays are reported elsewhere (25). After the collection of blood samples at week 12, the subjects discontinued the exemestane and left the study on tamoxifen.…”
Section: Methodsmentioning
confidence: 99%
“…However, in two preclinical models using human xenograft tumors in rodents [7,8] the steroidal AI exemestane, which irreversibly inhibits the aromatase enzyme, was shown to be more effective when combined with tamoxifen than either agent alone. In addition, two pilot clinical trials suggested that co-administration of tamoxifen does not affect exemestane pharmacokinetics or pharmacodynamics and that the combination is well tolerated and active [9][10][11].…”
Section: Introductionmentioning
confidence: 99%